Curbing Online Financial Scams in the Digital and AI Era: A Consumer Study - Mohammad Tahir Zainuddin; Natasya Aina Abdul Khadir; Muhamad Azrin Nazri; Wan Nur Fazni Wan Mohamad Nazarie (www.amertainstitute.com, 2024)
Along with the growing use of contemporary technologies, which has helped people in today's society with their daily lives but has led to an increase in online fraud instances that has cost consumers and service providers around the world significantly (Ali et al., 2019). Fraud is a deceptive act committed by a person with the intention to gain an unfair advantage or violate the rights of an individual. Malaysians have become victims and lost around RM415 million to scammers in the first seven months of 2022, which Bank Negara Malaysia intervened as the issue had gotten so bad (Nair, K., 2022). The goal of the study is to determine the elements that influence financial fraud victimization in Malaysian society by examining individuals' opinions towards various variables. Underpinned by fraud diamond theory to understand the psychology of the victims, the study investigates four hypotheses developed and tested in this study, i.e., Poor Knowledge, Low Self-Control, Financial Pressure and Bad Routine Activity, using a seven-point Likert scale ranging from 1 (strongly disagree) to 7 (strongly agree). The questionnaire is spread through social media sources and networking sites like WhatsApp and Telegram as well as Instagram. A total of 267 respondents were involved in this study, and quantitative data analysis employed IBM SPSS Software. The results gained after correlation and regression analysis proved the hypotheses, which the results of this study may give a clear direction in helping consumers from becoming victims of financial scams in the challenging economic environment.